Amskapi Pikuni : The Blackfeet People - Wissler, Clark, 1870-1947 (Book collections on Project MUSE., 2012)
A contemporary history of one of the best-known American Indian nations. Written in collaboration with Blackfoot tribal historians and educators, Amskapi Pikuni: The Blackfeet People portrays a strong native nation fighting for two centuries against domination by Anglo invaders. The Blackfeet endured bungling, corrupt, and drunken agents; racist schoolteachers; and a federal Indian Bureau that failed to disburse millions of dollars owed to the tribe. Located on a reservation in Montana cut and cut again to give land to white ranchers, the Blackfeet adapted to complete loss of their staple food, bison--a collapse of what had been a sustainable economy throughout their history. Despite all of these challenges, the nation held to its values and continues to proudly preserve its culture.